The Future of Islamic Financial Technology in Arab Countries (Journal of Economic Additions, 2025)
This study explores the future of Islamic financial technology in Arab countries by analyzing key concepts, recent developments, and opportunities for effective implementation in Islamic finance institutions. It examines the influence of FinTech on the banking sector, particularly its role in strengthening and developing Islamic banking. The analysis highlights how technological integration in Islamic financial institutions promotes financial inclusion and broadens access to services such as accounts, savings, payments, transfers, insurance, financing, and credit. The study emphasizes the potential of FinTech to modernize Islamic finance and expand its reach across diverse social segments.Jel Classification Codes :G21، G23، O33، Z12.
Keywords: Keywords : Financial technology, Islamic financial technology, Islamic financial industry, financial inclusion, Islamic financial institutions.